Prune Belly Syndrome: A Rare Case Report (Bangladesh Journal of Urology, 2020)
Prune belly Syndrome (PBS), a rare congenital anomaly of uncertain aetiologies has been seldom reported among Bangladeshis. Prune belly syndrome is a birth defect that involve three main problems like poor development of the abdominal musclescausing the skin of the belly area to wrinkle like a prune, undescended testicles and urinary tract problems. We report a case of 15 days old term male neonate with PBS. The baby named Shumon was admitted in Dhaka Medical College Hospital with complaint of lax abdominal wall, absence of both testes since birth. He was born by NVD and consulted with a local doctor who commented that the baby was not normal and referred to Dhaka Medical College Hospital for better management. On physical examination the baby weighted 2.7Kg and full length was 40 cm. He was mildly pale, his respiratory rate was 32 cycles per minute with normal breath sounds. Heart rate was 134 beats per minute. His abdomen was flabby with a wrinkled appearance and there were visible peristalses with palpable kidneys & bilateral undescended testes. His B.P was within normal range and cardiac examination was normal clinically and echocardiographically. USG of abdomen showed bilateral gross hydronephrosis with mega ureter. Micturating cystography showed grade-IV vesico-ureteric reflux bilaterally with no urethral obstruction. Serum creatinine concertration was 80 μmol/L, Serum Sodium was 130 mmol/L and Serum Potassium was 5.8 mmol/L. The presumptive diagnosis was Prune Belly Syndrome.Bangladesh Journal of Urology, Vol. 17, No. 1, Jan 2014 p.53-55